2016
DOI: 10.1097/tp.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Race Stratified Impact of Socioeconomics on Graft Outcomes in Kidney Transplant Recipients

Abstract: Background Socioeconomic status (SES) is a significant determinant of health outcomes and may be an important component of the causal chain surrounding racial disparities in kidney transplantation (KTX). The social adaptability index (SAI) is a validated and quantifiable measure of SES, with a lack of studies analyzing this measure longitudinally or between races. Methods Longitudinal cohort study in adult KTX transplanted at a single-center between 2005 and 2012. The SAI score includes 5 domains (employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Our approach identified this association and its contribution to the force of mortality in a direction consistent with prior experiences. Additionally, the results underscore the importance of social support and a greater degree of educational attainment as being protective for GL, which is consistent with our prior observations .…”
Section: Discussionsupporting
confidence: 91%
“…Our approach identified this association and its contribution to the force of mortality in a direction consistent with prior experiences. Additionally, the results underscore the importance of social support and a greater degree of educational attainment as being protective for GL, which is consistent with our prior observations .…”
Section: Discussionsupporting
confidence: 91%
“…Blacks are considered such a group, because the literature has clearly shown that they have a number of important factors that increase immunologic risks (10). These include lower rates of living donors, socioeconomic disadvantages, greater HLA mismatches, higher capacity to metabolize immunosuppressant medications, and polymorphisms that increase immunoreactivity (10)(11)(12)(13). Additionally, the aforementioned RCTs that assessed ESW safety contained disproportionately low numbers of blacks (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Hazard ratios for the risk of graft loss and death in early steroid withdrawal versus continued steroid (reference) stratified by modifying variables and time periods .83 to 0.97) 1 12. (1.02 to 1.24) 0.92 (0.86 to 0.99) 1.20 (1.05 to 1.36) 0.93 (0.86 to 0.99) 1.15 (1.01 to 1.30) 1.19 (1.06 to 1.33) 0.91 (0.85 to 0.98) .71 to 0.89) 1.11 (0.97 to 1.26) 0.83 (0.76 to 0.92) 1.22 (1.03 to 1.44) 0.81 (0.73 to 0.89) 1.26 (1.06 to 1.48) 1.05 (0.91 to 1.22) 0.86 (0.78 to 0.95) MMF, mycophenolate mofetil; MPA, mycophenolic acid; 95% CI, 95% confidence interval.…”
mentioning
confidence: 99%
“…These include risk factors for graft loss, such as medication nonadherence, changes in socioeconomics and/or health insurance and clinical events (cardiovascular disease and cancer). 12,13,23,38 It is likely that these are strong mediating factors that influence AA disparities. Thus, this analysis does not provide a fully comprehensive assessment of the predominant causes of racial disparities in transplant.…”
Section: Discussionmentioning
confidence: 99%